Meister Eckhart: close and remote. - Shabanova, Yuliya (Actual Problems of Mind, 2017)
The paper analyses the work by a medieval German gymnosophist Meister Eckhart whose ideas have found their second life in the irrationalistic conceptions of XIX-XX cc. The author concludes that all the temporal distance and notwithstanding his views are very twin to the Ukrainian philosophical thought.